Réponses

  • Utilisateur Brainly
2014-03-21T17:56:42+01:00
Résoudre les équation suivant :
8=-3x+7
3x=-1
x=-1/3

3x+15=-25+5x
-2x=-40
x=20

5x+6-3(7+2x)=4x+10
5x+6-21-6x=4x+10
-5x=25
x=-5

1-(3x-4)=5x-2(4x-5)

-3x+5=5x-8x+10
-6x=5
x=-5/6
Meilleure réponse !
2014-03-21T18:12:43+01:00
Résoudre les équations suivantes :

8 = -3x + 7
3x = - 8 + 7
3x = -1
x = -1/3

3x + 15 = -25 + 5x
3x - 5x = -25 - 15
-2x = -40
x = -40/-2
x = 20

5x + 6 - 3 (7 + 2x) = 4x + 10
5x + 6 - 21 - 6x = 4x +10
-11x = 25
x = 25/-11
x = -2,27

1 - (3x - 4) = 5x - 2(4x - 5)

-3x + 5 = 5x - 8x +10
-3x + 8x = -5 + 10
5x = 5
x = 5/5

x = 1